If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y+9)=2y-42
We move all terms to the left:
6(y+9)-(2y-42)=0
We multiply parentheses
6y-(2y-42)+54=0
We get rid of parentheses
6y-2y+42+54=0
We add all the numbers together, and all the variables
4y+96=0
We move all terms containing y to the left, all other terms to the right
4y=-96
y=-96/4
y=-24
| 9x(x-4)=-36 | | (6r-7)/1=r/4 | | -4=2x+2(x+4) | | -+-137=116-12x | | -25+7b=4b-1 | | 6(x+5)^2=0 | | (3x)(1x)=1625 | | 106=-8-6k | | -2(1/4)=r-4/5 | | 7(w-3)-5w=-13 | | 18x-9=5(2x+3) | | 3(4-x)=2(x+6) | | x+0.04x=3328 | | 2(3+x)=100 | | 2-8m=-6-12m | | 9x^2-24x=13 | | -3(x+7)=-2x-19 | | 5(2x-3)=3(x-19) | | F(x)=2x/3-15 | | 5n-2=-10+7n | | 5x^2+50x-68=-2 | | 14.2=14.2-x | | -6(x+4)=-42 | | 4(7x+6)=-4 | | 25=(7.2x)+.5*9.81*x^2 | | 4(2x-9)=5(3x-7)-1 | | 3500/n=50 | | 2^2-22=6x+5 | | 3(6-5x)=33 | | 0.3(r+2)=-0.1(-2r-4 | | -6a-2=2a-2 | | 10x-8=7+2 |